Introduction of Verticulture to Society in Pesawaran District, Lampung: a Community Empowerment - Marpaung, David Septian Sumanto; Fil’aini, Raizummi (CV. Multi Kreasi Media, 2026)
The problem of agricultural land use is compounded by rising housing demand. Potential development locations, such as Pesawaran District, attract visitors with their natural landscapes, which further increase housing demand while reducing available farmland. To address the issue of limited land use, verticulture—an urban agriculture technology—offers a promising solution. Verticulture is essentially a method of growing plants vertically. However, within the Pesawaran community, experience with verticulture remains limited. Therefore, introducing verticulture to society in Pesawaran is an important step toward achieving sustainable food production. In this study, verticulture knowledge was introduced to the Pesawaran community through presentations and demonstrations. A qualitative approach was employed, and data were analyzed using a pre-test/post-test design. The results indicate that verticulture knowledge was successfully conveyed to the community in Pesawaran District.